Piloting reusable plastic crates in the tomato value chain in Benin - Egah, Janvier; Hotegni, Nicodeme Fassinou; Kok, Melanie; Dijkxhoorn, Youri (Wageningen University & Research, 2025)
Do reusable plastic crates perform better compared to traditional baskets? The study highlights the challenges of introducing reusable plastic crates as an alternative packaging solution in South Benin’s tomato value chain. The study produced mixed outcomes, making it difficult to state that reusable plastic crates perform better compared to traditional baskets. Reusable plastic crates show potential for reducing post-harvest losses and increasing value in the tomato value chain, but their adoption faces challenges in cost and logistics, necessitating innovative business models for scalability. The results showed variability in post-harvest losses across packaging methods. While reusable plastic crates demonstrated slightly lower post-harvest losses compared to traditional baskets, the differences were not substantial. Loss percentages from farm to the retail level were inconsistent, with in some cases no clear trend favoring crates over traditional methods. Our study indicates a small opportunity to increase value across all stakeholders in the value chain by adopting improved packaging solutions. In the first round of assessments, four value chains demonstrated significantly higher monetary losses when using traditional baskets compared to reusable plastic crates. While crates preserved quality slightly better, the marginal improvement in prices did not offset the additional costs associated with the investment. Participants noted that the initial investment in crates posed a significant barrier, especially given the limited observed advantages during the pilot. Feedback highlighted logistical challenges with crate availability and the need for better integration into existing workflows. Some participants had concerns about limited tomato availability during the study period and this further complicated the data collection, particularly during the second round of data collection. Developing a sustainable business model for the returnable plastic crate intervention poses challenges. Implementing requires substantial investments, which are beyond the financial capacity of the participants. As a result, exploring alternative funding mechanisms or business models is essential to ensure the project's feasibility and long-term success.